2018
DOI: 10.1159/000490214
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Secreted by Human Urine-Derived Stem Cells Promote Ischemia Repair in a Mouse Model of Hind-Limb Ischemia

Abstract: Background/Aims: Our previous studies have shown that human urine-derived stem cells (USCs) have great potential as a cell source for cytotherapy and tissue engineering and that extracellular vesicles (EVs) secreted by USCs (USCs-EVs) can prevent diabetes-induced kidney injury in an animal model. The present study was designed to evaluate the effects of USCs-EVs on ischemia repair. Methods: USCs-EVs were isolated and purified by a battery of centrifugation and filtration steps. The USCs-EVs were then character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 59 publications
0
44
1
Order By: Relevance
“…One study reported that MSC-derived exosomes can mediate repair of kidney injury 23 , 24 . USCs also secrete exosomes, which were shown to protect against diabetic nephropathy 25 , promote of angiogenesis and wound healing in diabetic wound repair 26 , and promote the angiogenesis and muscle regeneration in hind-limb ischemia 27 . It is well known microRNAs (miRNAs) or small noncoding RNAs in exosomes play important roles in the regulation of target genes 28 .…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that MSC-derived exosomes can mediate repair of kidney injury 23 , 24 . USCs also secrete exosomes, which were shown to protect against diabetic nephropathy 25 , promote of angiogenesis and wound healing in diabetic wound repair 26 , and promote the angiogenesis and muscle regeneration in hind-limb ischemia 27 . It is well known microRNAs (miRNAs) or small noncoding RNAs in exosomes play important roles in the regulation of target genes 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, EVs isolated from ADMSCs limited the abnormal proliferation and migration of vascular smooth muscle cells, followed by neointimal hyperplasia in the setting of vein graft bypass surgery [164]. Administration of human UCMSC-EVs in a mouse model of hind-limb ischemia ameliorated severe ischemic injury, as revealed by increased limb perfusion and function [165]. With respect to tracheoesophageal diseases such as fistulas, ADMSC-EVs embedded in thermo-responsive hydrogels ensured the targeted delivery of EVs at the site of porcine oesophageal fistula; this, in turn, augmented healing.…”
Section: The Regenerative Effect Of Msc-evs On Various Tissuesmentioning
confidence: 99%
“…Since exosomes are nanosized, they can easily penetrate different bio barriers, including the blood-brain barrier. Hence, exosome-mediated therapy provides treatment of earlier distant foci of disease [61].…”
Section: Extracellular Vesicles Secreted By Udscsmentioning
confidence: 99%